ANDROID-BASED APPLICATION OF LPPM STMIK PRINGSEWU ARCHIVES TO IMPROVE DATA INTEGRATION OF LECTURER PERFORMANCE - Trisnawati Trisnawati; Sodikin Sodikin; M. Agus Badruzaman Al Khoir; Muhamad Muslihudin (Jurnal TAM (Technology Acceptance Model), 2021)
In the era of globalization, advances in information and communication technology affect human activities which have undergone many changes and developments. The development of science in the field of technology today has created new applications with more efficient technology productivity and costs. The rapid development of technology today has affected the work in various organizations. In order to support the performance in an organization, it is not only required the quality of reliable human resources but also required appropriate technological advances. All of this aims to provide convenience for technology users in carrying out their work. Applications that are built can be used via mobile phones or laptops based on browsers to display information in the form of text and images which are accessed using the internet. This application development uses waterfall model information system design and research flow uses Fishbone Mapping Chart model. The development of an Android-based LPPM STMIK Pringsewu Archive Data Application will be integrated with Lecturer Data so that it will facilitate monitoring and archiving Lecturer Data and increasing the Lecturer Performance Index at STMIK Pringsewu. Integrated data focuses on activities related to research and community service.